Evidence Based General Practice - M. M. Morales Suárez-Varela; Llopis-González, A.; Bell, J.; Tallón-Guerola, M.; Pérez-Benajas, A.; Carrión-Carrión, C. (European journal of epidemiology, 1999)
Objectives: to estimate the proportion of interventions in general practice that are based on evidence. Design: a one-year cross-sectional study involving all consultations by patients over age 15 years seen in 34 national primary health care centers. Setting: the rural Castellón provincial district within the Valencian Community in eastern Spain, with a total population of 21,155 inhabitants. Subjects: of 1990 case histories registered in the course of one year, 4800 consultations were identified; of these, 2341 (49%) distinct diagnosis-intervention pairs were identified and coded. Main results: the evidence basis for the diagnosis-intervention pairs in the study was derived from a computerized search of the scientific literature published in 1992-1996. The quality of the evidence was classified according to the method of Ellis et al. Within the 2341 diagnosis-intervention pairs, there was positive evidence in support of the intervention used in 55%. The evidence basis was sound for 42%, with 38% being based on Type I (clinical trials) evidence and 4% on Type II evidence. The most frequently presenting diseases involved the circulatory (18.7%), respiratory (14.9%), nervous (14.2%), musculo-skeletal (12.5%) and nutrition and metabolism and digestive systems, with 12.1% each. Conclusions: clinical practice was clearly supported by positive evidence of all Types (I-III) in a total of 55% of interventions, and by good positive evidence of Type I or II in 42% of interventions. The percentage of evidence-based interventions in general practice serving a substantial population in rural Spain was lower than had been reported by some authors.